Pengaruh Citra Merek, Harga, dan Kualitas Produk terhadap Keputusan Pembelian Paket Data Internet Telkomsel pada Mahasiswa - Annisa Amanda; Alhapen Ruslin Chandra; Tuti Azra (ABEC Indonesia, 2022)
The Internet is an electronic communication network that connects computer networks with computer facilities around the world. The use of data packages is an option to have access in cyberspace or the internet. One of the most popular brands of internet data package products today is the Telkomsel brand. Telkomsel internet data packages have a good brand image among the public with the prices offered vary according to the number of quotas. This study aims to determine how the influence of brand image, price, and product quality on students' decision to purchase Telkomsel internet data packages. The population in this study were Padang State Polytechnic students who had purchased and used Telkomsel internet data packages with a sample of 129 respondents. The sampling technique used in this research is accidental sampling. Data was collected using a questionnaire instrument which was distributed online to Padang State Polytechnic students. Data analysis in this study used multiple linear regression models. The results of this study partially indicate that the price and product quality variables have a positive and significant effect on purchasing decisions for Telkomsel internet data packages, while brand image variables have a positive and insignificant effect on purchasing decisions for Telkomsel internet data packages. Meanwhile, it simultaneously shows that the variables of brand image, price, and product quality have a significant effect on the decision to purchase Telkomsel's internet data package.